Diverging beliefs on climate change and climate policy in Germany: The role of political orientations - Leonard Knollenborg; Stephan Sommer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Using longitudinal data from two household surveys in 2017 and 2019, we analyze the determinants of climate skepticism in Germany. We find that nearly 20% of respondents state that they do not believe in climate change and more than 30% are doubtful that climate change is mainly caused by human action. Both percentages have increased over time. Moreover, we detect that political orientation is a crucial determinant for climate skepticism, as respondents inclined to Germany's right-wing populist party AfD are substantially more climate-skeptical and object to climate policies more frequently. One reason for the deviating beliefs may be rooted in the different trust in science, even if we can rule out that the lack of knowledge is a major factor. Consequently, our findings indicate a clear division in society on climate-related issues, one that would widen if the measures taken to combat climate change involved distributional consequences for AfD voters, as they already feel particularly burdened by energy costs. – – Anhand von Längsschnittdaten aus zwei Haushaltsbefragungen aus den Jahren 2017 und 2019 analysieren wir die Determinanten der Klimaskepsis in Deutschland. Unsere Ergebnisse zeigen, dass fast 20 % der Befragten angeben, nicht an den Klimawandel zu glauben und mehr als 30 % bezweifeln, dass der Klimawandel hauptsächlich durch menschliches Handeln verursacht wird. Beide Anteile haben im Laufe der Zeit zugenommen. Darüber hinaus stellen wir fest, dass die politische Orientierung eine entscheidende Determinante für Klimaskepsis ist, denn Befragte, die der rechtspopulistischen Partei AfD zugeneigt sind, sind wesentlich klimaskeptischer und lehnen die Klimapolitik häufiger ab. Ein Grund für die abweichenden Überzeugungen könnte in dem unterschiedlichen Vertrauen in die Wissenschaft liegen. Unsere Ergebnisse deuten also auf eine deutliche Spaltung der Gesellschaft in Klimafragen hin, die sich noch verstärken würde, wenn die Maßnahmen zur Bekämpfung des Klimawandels mit Verteilungskonsequenzen für AfD-Wähler, da sie sich durch Energiekosten ohnehin schon besonders belastet fühlen.
Keywords: H41; Q50; Q58; 330; Climate change mitigation; support; environmental policy; attitudes; survey data